Patients with chronic prostatitis/chronic pelvic pain syndrome show T helper type 1 (Th1) and Th17 self-reactive immune responses specific to prostate and seminal antigens and diminished semen quality - Motrich, Ruben Dario (2020)
Objectives: To assess the presence of self-reactive immune responses to seminal and prostate antigens (PAg), biomarkers of inflammation of the male genital tract, and semen quality parameters in patients with chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS). Patients, Subjects and Methods: Peripheral blood and semen samples were collected from patients with CP/CPPS and age-matched healthy control volunteers. We analysed the lymphoproliferative responses of peripheral blood mononuclear cells (PBMC) to different seminal plasma (SP)-derived and purified PAg, serum autoantibodies specific to PAg, leucocyte subpopulations, and inflammatory cytokines in semen, sperm apoptosis/necrosis, and semen quality parameters. Results: Significantly greater PBMC proliferative responses specific to PAg, with elevated secretion of interferon (IFN)γ and interleukin (IL)-17, were detected in the patients with CP/CPPS vs the controls. Moreover, the patients with CP/CPPS had significantly greater serum immunoglobulin G immune reactivity to SP proteins, such as prostate-specific antigen and prostatic acid phosphatase, than the controls. Inflammation of the male genital tract was exemplified by high levels of IFNγ, IL-17, IL-1β and IL-8, as well as higher counts of leukocytes, mainly CD4 T lymphocytes and macrophages, in the semen. In addition, this local inflammation was associated with an overall diminished semen quality, i.e., reduced sperm concentration, motility and viability; and higher levels of sperm apoptosis/necrosis in patients with CP/CPPS vs controls. Conclusion: Patients with CP/CPPS show T helper type 1 (Th1) and Th17 immune responses specific to PAg associated with chronic inflammation of the male genital tract and reduced semen quality. These immune responses may underlie the induction and development of chronic pelvic pain and inflammation of the male genital tract, which in turn could alter normal prostate functioning and impair semen quality.